Signatures of selection in recently domesticated macadamia - Lin, Jishan; Zhang, Wenping; Zhang, Xingtan; Ma, Xiaokai; Zhang, Shengcheng; Chen, Shuai; Wang, Yibin; Jia, Haifeng; Liao, Zhenyang; Lin, Jing; Zhu, Mengting; Xu, Xiuming; et al. (Nature communications, 2022)
Macadamia is a high value nut crop that is recently domesticated, ideal for testing the effect of artificial selection. Here, we sequence the genome of Hawaiian cultivar ‘Kau’ and assemble into 794 Mb in 14 pseudo-chromosomes with 37,728 genes. Genome analysis reveals a whole-genome duplication event, occurred 46.8 million years ago. Gene expansions occurred in gene families involves in fatty acid biosynthesis. Gene duplication of MADS-Box transcription factors in proanthocyanidin biosynthesis are relevant for seed coat development. Genome re-sequencing of 112 accessions reveals the origin of Hawaiian cultivars from Mount Bauple in southeast Queensland in Australia. Selective sweeps are detected in macadamia cultivars, including genes involved in fatty acid biosynthesis, seed coat development, and heat stress response. Such strong effects of artificial selection in few generations reveals the genomic basis for ‘one-step operation’ for clonal crop domestication. The knowledge gained could accelerate domestication of new crops from wild species. Macadamia is a recently domesticated nut crop. Here, the authors report the genome assembly of Hawaiian cultivar ‘Kau’ and conduct population genomic analyses to reveal the origin of Hawaiian cultivars and the genomic basis for one-step operation for the clonal crop domestication.